A friend in need: ICA and the National Archives of Malta. Issue 1 (1st December 2022) - Farrugia, Charles J.
Abstract : As any other NGO the ICA offers several benefits to its members. When one goes on the publicity literature of the organization, emphasis is made on the provision of a network of colleagues, specialized advice, and a tool kit of products and publications that come out of the organization. These are all noble benefits. But there are other political, psychological, and intangible benefits that such a network offers. This article celebrates the contribution of Charles Kecskemeti to the international archival domain through some personal reflections of what ICA membership has meant for Malta, for our National Archives and for me personally as an archivist.